Tensile properties and deformation mechanisms of a new Ni–Co base superalloy from room temperature up to 750 °C. (November 2022) - Xiao, Zhongrun; He, Junyang; Gu, Ji; Gan, Bin; Yu, Hongyao; Bi, Zhongnan; Du, Jinhui; Song, Min
Abstract: In this article, we developed a new Ni–Co base superalloy with excellent mechanical properties in the temperature region from room temperature to 750 °C. The yield and tensile strengths of the alloy at room temperature are ∼1212 MPa and ∼1638 MPa, respectively, and they can still reach ∼1077 MPa and ∼1233 MPa at 750 °C, maintaining a good intermediate temperature strength. Microstructure characterizations show that the plastic deformation is mainly dominated by anti-phase boundary (APB)-coupled dislocation pair shearing γ′ precipitates at room temperature. With increasing the temperature, although the dislocation pair shearing still dominates, stacking fault (SF) shearing and nanotwinning also appears and contributes minor to the plastic deformation. The interactions among dislocations, SFs and nanotwins finally results in the decent working hardening ability even at such a high temperature up to 750 °C, which in turn gives rise to the ultrahigh ultimate tensile strength of the Ni–Co base superalloy. Highlights: A new Ni–Co base superalloy with excellent mechanical properties up to 750°Cwas designed. The yield strength of the alloy remains stable up to 750 °C. The alloy can maintain a high UTS of 1233 MPa up to 750 °C. Dislocation pair shearing dominates the deformation, although SF shearing also contributes minor to the plastic deformation. The interactions among dislocations, SFs, and nanotwins results in the decent working hardening ability up to 750 °C.